Nujuh bulanan Tradition Value For Societies Resilience in Costumary Community Urug Bogor West Java - Fachruddin Majeri Mangunjaya; Bahagia Bahagia; Rimun Wibowo; Yono Yono (Lembaga penelitian dan pengabdian kepada Masyarakat, 2020)
The objective of this research is to investigate Nujuh Bulalanan tradition for resilience societies in customary societies. The method used is ethnography because of research related to societies, cultural, tradition and ritual of the community. Data are collected through in-depth interview with the leader of Urug societies, documentation and observation. The sample is selected using a purposive sampling technique. The result is analysed through triangulation which is mixing some gathering data method. The result is societies of Urug still pursue nujuh bulanan tradition. It can support cultural resilience because tradition from their forefather has not vanished amid globalisation of culture. Another finding is nujuh bulanan support societies resilience through mutual cooperation or mutual assisting. Activity is not the private activity but it is a common activity which is conducted by collective action and individual awareness which impact the collective consciousness. The impact is the societies who they live in the group are more resilience rather than life in an individual trait. The other finding is to create food resilience because local food which has been created by a group of societies can save a person from hunger when they receive local food in temporary periods. Besides, It can protect local traditional of food from extinction because in this tradition, societies typically women must invent local traditional food rather than another sort of food.